Strategi Pengambilan Keputusan Kepala Sekolah Berbasis Data dalam Meningkatkan Mutu Pendidikan di SD Negeri 11 Rantau Utara - Rambe, Lismawati (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to describe the principal’s strategies in utilizing school data, analyze data management processes for improving educational quality, examine the use of information technology in data-driven decision-making, and identify supporting and inhibiting factors at SD Negeri 11 Rantau Utara. The study employed a descriptive qualitative field research design. Data were collected through non-participant observation, semi-structured interviews, and documentation involving the principal, school operator, and teachers. Data were analyzed through data condensation, data display, and conclusion drawing, while validity was ensured through triangulation. The findings show that the principal’s strategies were systematic, goal-oriented, and aligned with school needs, reflecting transformational leadership that encouraged teacher collaboration. Data management was carried out continuously through collection, validation, processing, and interpretation as the basis for school policy formulation. The use of technology such as Dapodik, e-Rapor, and Education Report Cards improved efficiency by providing accurate and easily accessible data. Supporting factors included effective coordination, clear goals, data availability, and active participation of school members. The main obstacles were limited human resources, lack of training, communication barriers, and differences in understanding. Data-driven decision-making significantly contributed to improving educational quality